Indirect Effects of Oral Tolerance Inhibit Pulmonary Granulomas to Schistosoma mansoni Eggs. (13th October 2011) - Azevedo, Geraldo Magela; Costa, Raquel Alves; Resende, Mariana Araujo; Rodrigues, Claudiney Melquiades; Vaz, Nelson Monteiro; Carvalho, Cláudia Rocha
Abstract : Parenteral injection of tolerated proteins into orally tolerant mice inhibits the initiation of immunological responses to unrelated proteins and blocks severe chronic inflammatory reactions of immunological origin, such as autoimmune reactions. This inhibitory effect which we have called "indirect effects of oral tolerance" is also known as "bystander suppression." Herein, we show that i.p. injection of OVA + Al(OH)3 minutes before i.v. injection of Schistosoma mansoni eggs into OVA tolerant mice blocked the increase of pulmonary granulomas. In addition, the expression of ICAM-1 in lung parenchyma in areas outside the granulomas of OVA-orally tolerant mice was significantly reduced. However, at day 18 after granuloma induction there was no difference in immunofluorescency intensity to CD3, CD4, F4/80, and α -SMA per granuloma area of tolerant and control groups. Reduction of granulomas by reexposure to orally tolerated proteins was not correlated with a shift in Th-1/Th-2 cytokines in serum or lung tissue extract.